Oakland's Sugar-Sweetened Beverage Tax: Honoring the ?Spirit? of the Ordinance Toward Equitable Implementation (Mary Ann Liebert, 2021)
Purpose: On November 8, 2016, Oakland, California, voters passed a sugar-sweetened beverage (SSB) tax, which included language to support programs affecting communities and residents most affected by SSB-related health disparities. The purpose of this study was to qualitatively assess the extent to which those communities most affected by SSB-related health disparities were included in implementation decisions and were recipients of funding to support their needs. Methods: A longitudinal case study from 2016 to 2019 in Oakland, CA, explored equity implementation themes through key informant interview transcripts (n=15) triangulated with media (n=90) and archived documents (n=43). Using principals of constant comparative analysis, all documents (n=148) were coded and thematically analyzed in Atlas.ti. Results: SSB taxes?designed to support communities disproportionately impacted by SSB consumption?can be implemented with inclusivity and community representation. The Oakland ordinance established a Community Advisory Board (CAB) that partnered with community organizations throughout implementation to ensure inclusivity and recommend funding for programs to address health inequities, described as the ?spirit? of the ordinance. These activities countered the beverage industry's tactics to target lower income communities of color with misinformation campaigns and hinder implementation. Conclusion: A clearly written ordinance provides guidance, which affords an intentional and legal foundation for implementation processes. Establishing a CAB can mitigate inequities as members are invested in the community and initiatives to support residents. Advisory boards are able to liaise between city and local partners, which is a powerful tool for countering opposition campaigns, reaching lower income and communities of color, and ensuring adherence to funding mandates.